A Realist Defense of the Alien Tort Statute - Robert Knowles (Washington University Law Review, 2011)
This Article offers a new justification for modern litigation under the Alien Tort Statute (ATS), a provision from the 1789 Judiciary Act that permits victims of human rights violations anywhere in the world to sue tortfeasors in U.S. courts. The ATS, moribund for nearly 200 years, has recently emerged as an important but controversial tool for the enforcement of human rights norms. “Realist” critics contend that ATS litigation exasperates U.S. allies and rivals, weakens efforts to combat terrorism, and threatens U.S. sovereignty by importing into our jurisprudence undemocratic international law norms. Defenders of the statute, largely because they do not share the critics' realist assumptions about international relations, have so far declined to engage with the cost-benefit critique of ATS litigation and instead justify the ATS as a key component in a global human rights regime. This Article addresses the realists' critique on its own terms, offering the first defense of ATS litigation that is itself rooted in realism—the view that nations are unitary, rational actors pursuing their security in an anarchic world and obeying international law only when it suits their interests. In particular, this Article identifies three flaws in the current realist ATS critique. First, critics rely on speculation about catastrophic future costs without giving sufficient weight to the actual history of ATS litigation and to the prudential and substantive limits courts have already imposed on it. Second, critics’ fears about the sovereignty costs that will arise when federal courts incorporate international-law norms into domestic law are overblown because U.S. law already reflects the limited set of universal norms, such as torture and genocide, that are actionable under the ATS. Finally, this realist critique fails to overcome the incoherence created by contending that the exercise of jurisdiction by the courts may harm U.S. interests while also assuming that nations are unitary, rational actors. Moving beyond the current realist ATS critique, this Article offers a new, positive realist argument for ATS litigation. This Article suggests that, in practice, the U.S. government as a whole pursues its security and economic interests in ATS litigation by signaling cooperativeness through respect for human rights while also ensuring that the law is developed on U.S. terms. This realist understanding, offered here for the first time, both explains the persistence of ATS litigation and bridges the gap that has frustrated efforts to weigh the ATS’s true costs and benefits.
Keywords: Human rights; Sovereignty; Alien Tort Statute; United States